Dizziness handicap and anxiety depression among patients with benign paroxysmal positional vertigo and vestibular migraine. Issue 52 (24th December 2020) - Zhu, Cuiting; Li, Yiqing; Ju, Yi; Zhao, Xingquan
Abstract : Abstract: To investigate the dizziness handicap and anxiety depression among patients with benign paroxysmal positional vertigo (BPPV) and vestibular migraine (VM). A prospective cohort study in which patients came from the Department of Neurology, Beijing Tiantan Hospital, Capital Medical University was conducted. Patients were diagnosed with BPPV and VM from September 2016 to December 2017. Dizziness handicap inventory (DHI) scale and hospital anxiety and depression scale (HADS) were assessed among subjects before treatment and 3 months follow-up. We used the Mann–Whitney U test to compare the DHI and HADS scores of BPPV and VM patients before and after 3 months and found significantly statistical difference. Before treatment, the median DHI scores of BPPV and VM were 34 and 60, with a Z = −5.643 ( P  = .001); The median HADS scores were 6 and 14, with Z = −4.807 ( P  = .001). After 3 months follow-up, the median DHI scores of BPPV and VM were 0 and 22, with a Z = −8.425 ( P  = .001); The median HADS scores were 6 and 14, with Z = −7.126 ( P  = .001) 51.11% VM patients and 12.21% BPPV patients have anxiety and depression. A Spearman correlation revealed a significantly moderate positive correlation ( r  = .455, P  < .001) between DHI and HADS scores. The emotional, functional and physical effects of vertigo on VM patients were more significant than BPPV patients. The change of DHI scores in BPPV and VM patients was positively correlated with changes in the anxiety and depression in the HADS.